2007
DOI: 10.1038/ismej.2007.75
|View full text |Cite
|
Sign up to set email alerts
|

The geomicrobiology of gold

Abstract: Microorganisms capable of actively solubilizing and precipitating gold appear to play a larger role in the biogeochemical cycling of gold than previously believed. Recent research suggests that bacteria and archaea are involved in every step of the biogeochemical cycle of gold, from the formation of primary mineralization in hydrothermal and deep subsurface systems to its solubilization, dispersion and re-concentration as secondary gold under surface conditions. Enzymatically catalysed precipitation of gold ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
155
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 214 publications
(156 citation statements)
references
References 162 publications
(220 reference statements)
1
155
0
Order By: Relevance
“…( Figure 1; [11,12]). In a recent study, Tomkins [16] suggested that microbial processes may have had a far greater influence on the formation of orogenic gold deposits as previously believed.…”
mentioning
confidence: 99%
“…( Figure 1; [11,12]). In a recent study, Tomkins [16] suggested that microbial processes may have had a far greater influence on the formation of orogenic gold deposits as previously believed.…”
mentioning
confidence: 99%
“…The morphologies of bio-precipitated gold so closely resemble the gold found in contemporary (Australia) and paleoplacers, e.g., South Africa's Witwatersrand basin, that a biogenic origin for these auriferous deposits [8,9,18,19] is now accepted.…”
Section: Introductionmentioning
confidence: 95%
“…The biogeochemical cycling of precious metals and the formation of certain geologic deposits can be attributed to microbial activity [8][9][10][11][12]. In vitro studies have shown that bacteria are able to immobilize and/or precipitate gold from gold-rich solutions [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations